Robust video watermarking based on dual-plane correlation for immunity to rotation, scale, translation, and random distortion - Atomori, Y.; Echizen, I.; Dainaka, M.; Nakayama, S.; Yoshiura, H. (Journal of Digital Information Management, 2008)
A robust video watermarking method is described that can embed watermarks immune to not only rotation, scaling, and translation but also to random geometric distortion and any of their combinations. It can detect watermarks without any search for canceling the effect of random distortion. Rotation, scale, and translation are canceled by searching for the angle, size, and origin of the original picture. The search for the angle and size is combinatorial but is independent of the search for the origin. That is, the angle and size of the target picture can be restored without restoring the picture's origin. Furthermore, the search for the origin is divided into horizontal and vertical searches that can be carried out independently. The number of searches is thus drastically reduced, making the processing speed high enough for practical application. Experimental evaluation using actual video samples demonstrated that the proposed method can embed watermarks immune to all four types of transformations.
Keywords: Random distortion; RST; Survivability; Video watermarking